Famine of 1943 in Bakarganj and British Colonial Policy. (December 2021) - Islam, Muhammad Saiful; Zisan, Tasnuva Habib
In the vast literature of Bengal famine of 1943, it is hard to offer new insights about that vicious source of mass misery. Local history may mark a significant departure here, as it provides scope for an in-depth study of both the origin and course of the famine. Bakarganj was called the granary of Bengal, which used to supply rice to other regions even in the driest years due to its large production. But the famine of 1943 gravely affected this district. The present study shows how it was the colonial measures that played a vital role in intensifying the famine in Bakarganj. The government's led to: hoarding of rice and serious shortage of food supply. The article concentrates on four aspects of the government failure: inappropriate warning system, callous purchase policy, lack of effective government inspection and a policy of disaster denial.